MODEL FOR ADMINISTRATIVE SECURITY MANAGEMENT IN A MUNICIPALITY: MODEL FOR ADMINISTRATIVE SECURITY MANAGEMENT IN A MUNICIPALITY - Simeonova, Iliana; Metodieva, Tsvetelina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
Administrative security is critical to the effective functioning of government organisations. It is an attest component of governance and plays a key role in protecting public institutions. Bulgaria, with its distinctive geopolitical and historical context, represents a unique environment for exploring the conceptuality of administrative security and its functionality. Understanding and assessing administrative security is essential for the development and stability of the country.